EHL-İ SÜNNET USULUNDEKİ KIYASLA Şİİ CAFERİLER'DEKİ AKLIN MUKAYESESİ - ERGÜVEN, NİZAMETTİN (Fırat Üniveristesi, 2004)
Ehl-i Sünnet and Şia are the big scholl in islamic reflection. I studied the kıyas in Ehli Sünnet intelligence end Şia. At first I examine kıyas as an evidence and than I studied intelligence and the and of the study I examine kıyas and intelligence between this two scholls. Each one was says what, and if there were any resemble and difference between them. Ehli Sünnet takes kıyas as a fourth evidence in Şeriah and Şia takes intelligence as a fourth evidence. We can say kıyas in Ehli Sünnet and intelligence in Şia is both nearness things if w emay say union idea between them we also use the içtihad term. Both kıyas and intelligence participate in içtihat. 86
Comparison of analogy in Ahli Sunnah and intelligence in Şiah Methodology
Keywords: Din; Religion